Student challenging behavior with a positive behavior support training for teachers: A case study - Hasna Pratiwi Kuswardani; Pramesti Pradna Paramita (Institute of Advanced Engineering and Science, 2023)
Challenging behavior is repetitive behavior that risks interfering with learning or involvement in prosocial interactions. Challenging behaviors are often shown by students and difficult to manage, such as: defiance and noncompliance, destruction, disruption, physical aggression, self-injury, social withdrawal, socially inappropriate behavior, stereotypes, and verbal aggression. One of the ways of good classroom management is through Tier 1 Positive Behavior Support (PBS) training. It is very necessary for students and teachers when they are in the school environment because it can create a conducive classroom atmosphere. Therefore, the researcher designed a Tier 1 PBS training program that focuses on the teacher’s ability to manage the classroom using a proactive strategy as opposed to a reactive strategy. The subjects of this training were seven teachers of Islamic junior high school in Central Java, Indonesia. The experimental design was conducted without using a control group and using pre-test and post-test for evaluation. The findings indicated that Tier 1 PBS training is effective in increasing the ability of teachers to use proactive classroom management strategies and reducing the use of reactive classroom management strategies.